The Continuity of the Nusantara Islamic Tradition in Saudi Arabia A Case Study of Students of Indonesian Descent in Jeddah - Habiba Mafaza Zein; Auliya Ridwan; Helvi Rahmi Azwar (Tebuireng: Journal of Islamic Studies and Society, 2025)
Abstrak This study aims to explore the forms and dynamics of the continuity of the Nusantara Islamic tradition among students of Indonesian descent in Jeddah, Saudi Arabia. It also analyzes how these students negotiate their cultural and religious identities within the context of diaspora. Employing a descriptive qualitative approach, data were collected through observations and in-depth interviews with students and teachers at the Indonesian School in Jeddah (SIJ). The findings reveal that traditions such as tahlilan, yasinan, the celebration of the Prophet’s birthday (Maulid Nabi), and family religious gatherings continue to be practiced in adaptive ways within private and limited spaces. These findings are analyzed using Stuart Hall’s theory of identity, which views identity as a negotiated and socially constructed process. The students in the diaspora context form a fluid and hybrid Islamic identity, blending the inherited values of the Nusantara Islamic tradition with the conservative religious norms prevalent in their surrounding environment. This study contributes to the discourse on Islamic moderation and the preservation of cultural identity in transnational contexts. It also highlights the importance of contextualized educational approaches for diaspora communities in sustaining the values of Nusantara Islam.